Trends and characteristics of suspected measles outbreaks in Lumajang during 2022 - Tri Damayanti Simanjuntak; Adistha Eka Noveyani; Isa Ma'rufi (Science Midwifery, 2023)
Measles is a highly contagious, acute illness that can transmit the measles virus close to 100% of susceptible contacts and can cause fatalities. This study aimed to describe the trend and distribution of the characteristics of the suspected measles outbreak in Lumajang regency during 2022. This research used secondary data. The sampling technique used was total sampling, with the inclusion criteria of all suspected measles cases included in the scope of the Lumajang District Health Office in 2022, namely 49 people. This study used univariate analysis to describe the trend of suspected measles and the frequency distribution of the characteristics of suspected measles. Epi Info version 7.2.5.0 is used for the analysis process. The results showed that 100% of suspected measles had a fever and developed a maculopapular rash. Other symptoms that often appeared in suspected measles were cough and runny nose, approximately 14.29%. 49 people were suspected of measles cases with 53% women and 47% men. Rogotrunan Primary Healthcare was the most 43.69% suspected source. Nearly half of suspected measles came from the age group 1-4 years (42.86%), Where the 1-year-old was the youngest up to 60 years old was the oldest. Of the 49 suspected measles, one-third (32.65%) had incomplete immunization status. The primary healthcare with the highest suspected measles rate was the primary healthcare with the measles-rubella immunization coverage not reaching the national target of 90%. The timely identification of measles cases is crucial. Active surveillance for measles disease should be conducted for every confirmed measles case to assure timely reporting of suspected cases in the population known to be affected as well as other segments of the community that may be at high risk of exposure or in low vaccination coverage.